Compression garments reduce muscle movement and activation during submaximal running - Broatch, J. R.; Brophy-Williams, N.; Phillips, E. J.; O'Bryan, S. J.; Halson, S. L.; Barnes, S.; Bishop, D. J. (Medicine & Science in Sports & Exercise, 2020)
PURPOSE: The purpose of this study was to investigate the effectiveness of sports compression tights in reducing muscle movement and activation during running. METHODS: A total of 27 recreationally active males were recruited across two separate studies. For study 1, 13 participants (mean ± SD = 84.1 ± 9.4 kg, 22 ± 3 yr) completed two 4-min treadmill running bouts (2 min at 12 and 15 km·h) under two conditions: a no-compression control (CON1) and compression (COMP). For study 2, 14 participants (77.8 ± 8.4 kg, 27 ± 5 yr) completed four 9-min treadmill running bouts (3 min at 8, 10, and 12 km·h) under four conditions: a no-compression control (CON2) and three different commercially available compression tights (2XU, Nike, and Under Armor). Using Vicon 3D motion capture technology, lower limb muscle displacement was investigated in both study 1 (thigh and calf) and study 2 (vastus lateralis + medialis [VAS]; lateral + medial gastrocnemius [GAS]). In addition, study 2 investigated the effects of compression on soft tissue vibrations (root-mean-square of resultant acceleration, RMS Ar), muscle activation (iEMG), and running economy (oxygen consumption, V.O2) during treadmill running. RESULTS: Wearing compression during treadmill running reduced thigh and calf muscle displacement as compared with no compression (both studies), which was evident across all running speeds. Compression also reduced RMS Ar and iEMG during treadmill running, but it had no effect on running economy (study 2). CONCLUSION: Lower limb compression garments are effective in reducing muscle displacement, soft tissue vibrations, and muscle activation associated with the impact forces experienced during running.